Morphological evaluation and diagnosis of medial type osteoarthritis of the knee using ultrasound - Yanagisawa, Shinya; Ohsawa, Takashi; Saito, Kenichi; Kobayashi, Tsutomu; Yamamoto, Atsushi; Takagishi, Kenji (Journal of orthopaedic science : official journal of the Japanese Orthopaedic Association, 2014)
The aim of this study was to diagnose osteoarthritis (OA) of the knee joint using ultrasound (US). The study subjects included 27 males and 54 females (131 knees), who had a mean age of 62.8 years. US was used to evaluate the medial joint space of both knees in complete extension with and without weightbearing. In each patient, the medial radial displacement of the medial meniscus (MRD), the peripheral joint space (PJS) and the number of osteophytes were evaluated. The subjects were divided into five groups based on the KL grade (0-4), and then each value was compared. Additionally, the subjects were divided into two groups: KL grade 0 and 1 (non-OA group) and KL grade 2-4 (OA group). We classified patients who met the following criteria as having OA on the US assessment: <5 mm of PJS during weight-bearing, >5 mm of MRD during weight-bearing, and >2 mm of osteophytes. Then we examined the diagnostic accuracy of the radiographic diagnosis (non-OA or OA of the knee) using US assessment. The PJS was significantly decreased and the MRD was significantly increased in the OA group compared to the non-OA group (p < 0.001). The percentage of radiographic OA of the knee that was correctly diagnosed by ultrasound was 90.8 % (sensitivity), with a specificity of 95.5 %. The positive predictive value was 97.5 % and the negative predictive value was 84.0 %. Our study therefore showed that US has both a high reliability and excellent diagnostic accuracy.